Studies on the antibacterial potentials and phytochemical properties of Tectona grandis leaf extracts on some bacterial isolates (Kuwait Journal of Science)
The study aimed to evaluate the antibacterial effects of the crude extracts and partially purified fractions from Tectona grandis (teak) leaves on various clinical and environmental bacterial isolates, as well as to determine the plant's phytochemical components. The crude extract of Tectona grandis leaf powder (TgCE) was obtained by maceration in methanol, concentration, and then partitioning into n-hexane, dichloromethane (DCM), ethyl acetate, and aqueous methanol fractions (in increasing order of polarity). The extract and fractions were assayed on the bacterial isolates under study together with standard antibiotics as reference. Antibacterial efficacy was evaluated using the agar-well diffusion method, and the rate of kill of the active n-hexane and ethyl acetate fractions was assessed on the Gram-positive and negative bacteria that were most susceptible to these fractions. Phytochemical analysis was carried out on the crude methanol extract, and the toxicity assay was performed usingthe brine shrimp test. Results showed that TgCE maintained high activity at 35 mg/ml concentration (P < 0.001), against most test bacteria that exhibited multiple antibiotic resistance index (MARI) greater than 0.2 and up to 0.75 when exposed to standard antibiotics. The minimum inhibitory concentration (MIC) of the crude extract ranged from 0.55 to 4.38 mg/ml while the minimum bactericidal concentration (MBC) range was 1.09 to 8.75 mg/ml. The most active fractions were the n-hexane and ethyl acetate, with MBC/MIC ratio ranges of 1.98 to 2.01 which is indicative of bactericidal activity, and also, the bacterial kill accumulated with increase in concentration of these fractions and time. Phytochemicals present in T. grandis include flavonoids, alkaloids, terpenoids, tannins, sterols, saponins, phenols, and anthroquinones, and from the toxicity analysis, its LC50 (lethal concentration 50) was estimated at 71.02 mg/ml. In conclusion, the crude extract and fractions of Tectona grandis leaf possess potent antibacterial properties that can be explored as important resource for the synthesis of de novo antibiotics with future relevance in the therapeutic management of infectious diseases. © 2025